(3OQGSI ebGQfI Hjf GdfXGe GdeUQaj GdJbdjOj hGdfXGe GdeUQaj GdESdGejs - (3edjcI(B, (3SYjO Hf YdbeIs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2022)
(3eONd ddgfOSI GdeGdjI ef GdefXhQ GdeUQaj GdJbdjOj hGdESdGej, eaGgje YGeI Mhd GdgfOSI GdeGdjI, GdgfOSI GdeGdjI GdESdGejI, COhGJ GdESJKeGQ aj GdShb GdeGdjI GdJbdjOjI hGdESdGejI, YedjGJ GdJhQjb ef GdefXhQ GdeUQaj GdJbdjOj, eaGgje YGeI Mhd GdJhQjb GdJbdjOj, GdeJNdhf aj YedjI GdJhQjb hgjGcd GdEUOGQGJ, BdjGJ YedjGJ GdJhQjb, YedjGJ GdJhQjb ef GdefXhQ GdeUQaj GdESdGej (B-(3YedjGJ GdJUcjc(B- (3, YehejGJ Mhd GdJhQjb GdESdGej, GdeYGdLI GdeMGSHjI dYedjGJ GdJUcjc hCfhGY GdUchc GdESdGejI hCgejJgG , GdhUa GdTQYji dWQb GdJhQjb hGdeNGWQ GdeQJHWI HYedjI GdJUcjc, ebGQfI Hjf fehPL GdJhQjb GdJbdjOj hfehPL GdJhQjb GdESdGej, GdJMOjGJ GdJj JhGLg YedjGJ GdJhQjb GdESdGejebGQfI HGdJhQjb GdJbdjOj, eYjGQ caGjI QCS GdeGd ddeUGQa GdESdGejI , ebGQfI Hjf BdjGJ GdJhQjb GdJbdjOj hGdJhQjb GdESdGej(B.s
(3eQGLY U(B.629 (3edGMb U(B.667s
Keywords: (3GdChQGb GdeGdjIs; (3GdHfhc GdGSdGejIs; (3GdJhQjbs; (3GdSjGSI GdeGdjIs; (3GdfXGe GdfbOjs